IMPACT OF THE DIGITALIZATION PROCESS ON PSYCHOLOGICAL CHARACTERISTICS OF PERSONALITY - Burkaltseva, D.; Timoshenko, O.; Golynsky, V.; Dymanova-Golynskaya, T.; Savchenko, L.; Niyazbekova, S.; Guk, O. (Scientific Journal of Pedagogy and Economics, 2020)
Over the past twenty years, a new stage and new conditions of development in humanity – digitalization emerged. Digitalization affects absolutely all spheres of life. The purpose of the study is to consider the impact of the digitalization process on psychological characteristics of personality.